2017
DOI: 10.1186/s12957-016-1094-z
|View full text |Cite
|
Sign up to set email alerts
|

CMTM1_v17 is associated with chemotherapy resistance and poor prognosis in non-small cell lung cancer

Abstract: BackgroundConsidering neoadjuvant chemotherapy (NAC) prior to surgery could shrink and reduce the primary tumor and distant micro-metastases to reduce the high relapses rates, NAC has been an accepted therapeutic management for patients with non-small cell lung cancer (NSCLC). CMTM1_v17 is highly expressed in human testis tissues and solid tumor tissues but relatively low expression was obtained in the corresponding normal tissues. This study aims to investigate the significance of CMTM1_v17 in NSCLC and its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The study demonstrated that CMTM1-v17 enhanced the cellular proliferation of breast cancer and prevented TNF-a-induced apoptosis by activating the NF-kB pathway. Si et al discovered that CMTM1-v17 levels in non-small cell lung carcinoma groups was much higher than in parocarcinoma tissue, which might promote the chemoresistance and lead to poor prognosis (45). Additionally, CMTM1 promoted glioblastoma cells (A172 and U251MG) proliferation and invasion which have already been verified through in vitro experiments (46).…”
Section: Cmtm1mentioning
confidence: 94%
“…The study demonstrated that CMTM1-v17 enhanced the cellular proliferation of breast cancer and prevented TNF-a-induced apoptosis by activating the NF-kB pathway. Si et al discovered that CMTM1-v17 levels in non-small cell lung carcinoma groups was much higher than in parocarcinoma tissue, which might promote the chemoresistance and lead to poor prognosis (45). Additionally, CMTM1 promoted glioblastoma cells (A172 and U251MG) proliferation and invasion which have already been verified through in vitro experiments (46).…”
Section: Cmtm1mentioning
confidence: 94%
“…The effect of CMTM1_v17 on neoadjuvant chemotherapy (NAC) has been evaluated in a clinical study in a cohort of 78 patients with NSCLC previously treated with NAC and surgery. The expression level of CMTM1_v17 was positively correlated with higher pathological staging and lower partial response rates, thus suggesting that CMTM1_v17 expression may cause chemoresistance 15 . Moreover, Cox regression analysis indicated that expression of CMTM1_v17 in tumor tissue after NAC is an independent prognostic risk factor, and patients with high expression have poorer overall and disease-free survival outcomes than those with low expression 15 .…”
Section: The Potential Clinical Value Of the Cmtm Familymentioning
confidence: 98%
“…The CMTM family has been reported to have considerable clinical value for accessing pathological stages, determining therapeutic strategies, and predicting the outcomes of many cancer types, including breast cancer, NSCLC, and gastric cancer 15 , 16 , 42 .…”
Section: The Potential Clinical Value Of the Cmtm Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that CMTM1_v17 is also highly expressed in a variety of solid tumors (breast cancer, kidney cancer, lung cancer, and ovarian cancer) and that it can activate nuclear factor-kappa B (NF-κB) signaling to promote cell proliferation and partially resist apoptosis induced by tumor necrosis factor-α [41]. Additionally, CMTM1_v17 expression is strongly linked with chemotherapy resistance and poor prognosis in early stage NSCLC patients who have received neoadjuvant chemotherapy [49]. Protein Atlas search found that lower CMTM1 expression was associated with a higher survival probability in both lung squamous cell carcinoma and adenocarcinoma (Figure 1).…”
Section: Cmtm1 and Nsclcmentioning
confidence: 99%